Probabilistic temporal databases, I algebra. - Dekhtyar, Alex (ACM transactions on database systems.)
Dyreson and Snodgrass have drawn attention to the fact that, in many temporal database applications, there is often uncertainty about the start time of events, the end time of events, and the duration of events. When the granularity of time is small (e.g., milliseconds), a statement such as ?Packet p was shipped sometime during the first 5 days of January, 1998? leads to a massive amount of uncertainty (5×24×60×60×1000) possibilities. As noted in Zaniolo et al. [1997], past attempts to deal with uncertainty in databases have been restricted to relatively small amounts of uncertainty in attributes. Dyreson and Snodgrass have taken an important first step towards solving this problem. In this article, we first introduce the syntax of Temporal-Probabilistic (TP) relations and then show how they can be converted to an explicit, significantly more space-consuming form, called Annotated Relations. We then present a theoretical annotated temporal algebra (TATA). Being explicit, TATA is convenient for specifying how the algebraic operations should behave, but is impractical to use because annotated relations are overwhelmingly large. Next, we present a temporal probabilistic algebra (TPA). We show that our definition of the TP-algebra provides a correct implementation of TATA despite the fact that it operates on implicit, succinct TP-relations instead of overwhemingly large annotated relations. Finally, we report on timings for an implementation of the TP-Algebra built on top of ODBC.